The electronics, online trigger system and data acquisition system of the J-PARC E16 experiment. Issue 8 (December 2015) - Takahashi, T N; Hamada, E; Ikeno, M; Kawama, D; Morino, Y; Nakai, W; Obara, Y; Ozawa, K; Sendai, H; Tanaka, M M; Uchida, T; Yokkaichi, S
Abstract: The J-PARC E16 experiment was proposed to investigate the restoration of chiral symmetry at the normal nuclear density. E16 will systematically measure in-medium mass of vector mesons at J-PARC Hadron Experimental Facility using a 30-GeV proton beam with an intensity of 2 x 10 10 protons per pulse. The E16 spectrometer was designed to detect e + e - from slowly moving vector meson, particularly the ϕ meson. The detector system consists of GEM tracker, Gas Cerenkov detector based on GEM and electromagnetic calorimeter made of lead-glass, whose number of channels reaches about 100, 000 in total. The readout electronics, trigger system and data acquisition system for the detectors have been developed, for which level-1 trigger rate of 1-2 kHz is required under several 10 MHz interaction rate. The preparation is underway for the first beam time in 2017.